Pulmonary resident memory T cells in respiratory virus infection and their inspiration on therapeutic strategies - Zhang, Meng; Li, Na; He, Yanchao; Shi, Tianyun; Jie, Zhijun (Frontiers in Immunology, 2022)
The immune system generates memory cells on infection with a virus for the first time. These memory cells play an essential role in protection against reinfection. Tissue-resident memory T (TRM) cells can be generated in situ once attacked by pathogens. TRM cells dominate the defense mechanism during early stages of reinfection and have gradually become one of the most popular focuses in recent years. Here, we mainly reviewed the development and regulation of various TRM cell signaling pathways in the respiratory tract. Moreover, we explored the protective roles of TRM cells in immune response against various respiratory viruses, such as Respiratory Syncytial Virus (RSV) and influenza. The complex roles of TRM cells against SARS-CoV-2 infection are also discussed. Current evidence supports the therapeutic strategies targeting TRM cells, providing more possibilities for treatment. Rational utilization of TRM cells for therapeutics is vital for defense against respiratory viruses.